2010
DOI: 10.1016/j.ejcts.2009.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Echo rejection score: new echocardiographic approach to diagnosis of heart transplant rejection☆

Abstract: Our proposed method for screening patients at risk of acute cardiac rejection with echo rejection score showed a good sensitivity in detection of graft rejection. However, further study is required to determine if it can be used as an adjunct to the myocardial biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
1
14
1
1
Order By: Relevance
“…Marciniak et al 11 found RV free wall strain to be significantly reduced in those with ACR degree $ 1B, 3 in basal and apical segments. Roshanali et al 13 studied RV basal free wall strain and found a nonsignificant reduction in patients with ACR degree $ 3A. 3 In our study, RV free wall strain < 17% was related to a significant degree of ACR, with sensitivity of 85.7%, specificity of 91.1%, and NPV of 98.8%.…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…Marciniak et al 11 found RV free wall strain to be significantly reduced in those with ACR degree $ 1B, 3 in basal and apical segments. Roshanali et al 13 studied RV basal free wall strain and found a nonsignificant reduction in patients with ACR degree $ 3A. 3 In our study, RV free wall strain < 17% was related to a significant degree of ACR, with sensitivity of 85.7%, specificity of 91.1%, and NPV of 98.8%.…”
Section: Discussioncontrasting
confidence: 44%
“…In three studies assessing DTI-derived deformation parameters, ACR was associated with a significant reduction in peak systolic longitudinal and radial strain. [11][12][13] Marciniak et al 11 found a decrease in longitudinal strain in both the right and left ventricles in grade $ 1B ACR. 3 However, in their cohort, the parameter with the best accuracy was radial strain, with a cutoff value of 30%.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Three smaller studies have also demonstrated that Em significantly reduced in allograft rejection (23,38,39). On the other hand, other studies on 1500 biopsies in nearly 450 patients reported no association between acute allograft rejection and Em (40)(41)(42)(43)(44)(45)(46). Our study found that both tricuspid and mitral annular early (Em), but not late (Am), diastolic velocities were significantly different in the patients with acute allograft rejection.…”
Section: Discussionsupporting
confidence: 44%